2007
DOI: 10.1002/cne.21328
|View full text |Cite
|
Sign up to set email alerts
|

Nonintegrin laminin receptor precursor protein is expressed on olfactory stem and progenitor cells

Abstract: The biochemical identification and immunocytochemical characterization of a cell surface antigen, expressed on globose basal cells (GBCs) of the rodent olfactory epithelium (OE), are described. The monoclonal antibody (MAb) GBC-3 recognizes a surface protein, confirmed by both live cell staining and fluorescence-activated cell sorting. Two-dimensional SDS-PAGE/Western blot followed by tandem mass spectrometry demonstrates that the cell surface GBC-3 antigen is the 40 kDa laminin receptor precursor protein. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 35 publications
0
34
0
Order By: Relevance
“…We also examined the chromatin state of OR genes in other progenitor cells from the MOE that are negative for OMP, ICAM-1, iLR (immature laminin receptor) (another marker for multipotent basal cells (Jang et al, 2007)) and SUS4. As seen in Figure 4G, in this population the enrichment for H3K9me3 and H4K20me3 on the tested ORs is as high as in the OMP + cells.…”
Section: Resultsmentioning
confidence: 99%
“…We also examined the chromatin state of OR genes in other progenitor cells from the MOE that are negative for OMP, ICAM-1, iLR (immature laminin receptor) (another marker for multipotent basal cells (Jang et al, 2007)) and SUS4. As seen in Figure 4G, in this population the enrichment for H3K9me3 and H4K20me3 on the tested ORs is as high as in the OMP + cells.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that mammal olfactory epithelium (OE) consisted of olfactory receptor neurons, supporting cells, global and horizontal basal stem cells, which have been demonstrated to be responsible for replacing damaged cells (Chen et al 2004, Jang et al 2007). Therefore, OE has been considered to be an essential source for adult neural progenitor cells.…”
Section: Introductionmentioning
confidence: 99%
“…Non-integrin laminin receptor precursor protein is expressed in the olfactory stem and progenitor cells. 14 are expressed in the olfactory epithelium, 15,16 and their expression increases in the olfactory epithelium 15,17 and olfactory bulb. 18 Plasmin may play a role in degrading laminin and activating matrix metalloproteinases.…”
Section: Discussionmentioning
confidence: 99%